Behavior of carbon fiber-reinforced recycled concrete aggregate. Issue 5 (5th July 2017) - Li, M.; He, H.; Senetakis, K.
Abstract : The behavior of a uniform recycled concrete aggregate (RCA) reinforced with carbon fibers is examined in the study. Six specimens with percentages of fiber from 0% to 2% were prepared in a triaxial apparatus and tested using bender elements. These specimens followed an anisotropic stress path after their initial consolidation at isotropic pressures of 100 or 500 kPa. Additionally, 19 specimens with fiber content equal to 0%, 1% and 2% were prepared in the triaxial apparatus and their large deformation behavior was quantified. The results indicated that at very small strains, the shear modulus of the fiber-reinforced samples was reduced in comparison to the unreinforced RCA samples. In terms of the effect of stress anisotropy on the shear modulus of the samples, firm conclusions could not be drawn with respect to the role of fiber content from this limited testing series. At larger strains, the reinforced and unreinforced samples showed relatively similar stress–strain response and volumetric behavior, with very similar critical state parameters in terms of ( λ ) and (Γ). The reinforcement with fibers increased the critical state angle of shear strength from about 33.5 to about 36.0° as the content of fibers increased from 0% to 2%.